1978
DOI: 10.1161/01.res.42.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Changes in central catecholaminergic neurons in the spontaneously (genetic) hypertensive rat.

Abstract: SUMMARY Catecholamines and catecholamine-synthesizing enzymes have been examined in specific brain areas during the development of spontaneously (genetic) hypertensive (SH) rats. Changes in catecholamine metabolism were localized to regions of the brain implicated in the regulation of blood pressure. Norepinephrine levels and dopamine-/3-hydroxylase (DBH) activities were decreased in specific nuclei of the hypothalamus and in the nucleus interstitialis striae terminalis ventralis, in both young and adult rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

1979
1979
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(63 citation statements)
references
References 31 publications
2
60
0
1
Order By: Relevance
“…Several studies suggest, however, an abnormality in central adrenergic pathways, which results in either excessive activity of excitatory centers or inadequate activity of inhibitory centers. Saavedra et al 19 have recently shown a reduction in dopamine-beta-hydroxylase activity and norepinephrine levels in specific nuclei of the hypothalamus, as well as abnormally high activity of phenylethanolamine-N-transferase in the brain stem of the SHR. We have recently demonstrated that Ldopa, presumably by increasing catecholamine levels in certain areas of the brain, is a potent depressor agent in the SHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest, however, an abnormality in central adrenergic pathways, which results in either excessive activity of excitatory centers or inadequate activity of inhibitory centers. Saavedra et al 19 have recently shown a reduction in dopamine-beta-hydroxylase activity and norepinephrine levels in specific nuclei of the hypothalamus, as well as abnormally high activity of phenylethanolamine-N-transferase in the brain stem of the SHR. We have recently demonstrated that Ldopa, presumably by increasing catecholamine levels in certain areas of the brain, is a potent depressor agent in the SHR.…”
Section: Discussionmentioning
confidence: 99%
“…The precise location(s) within the CNS of the abnormalities leading to excessive SNA remains unknown, although several recent studies suggest involvement of the hypothalamus and/or the brain stem. 19 ' m Similarly, the neurochemical basis of the CNS abnormality is unknown. Several studies suggest, however, an abnormality in central adrenergic pathways, which results in either excessive activity of excitatory centers or inadequate activity of inhibitory centers.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that differences in this parameter emerge at a later stage31, ~z. It should be noted that Saavedra et al 22 reported a decreased noradrenaline concentration in various hypothalamic nuclei of both 4-and 14-week-old SH-rats as compared with WK-rats of the same age. The reason for these discrepancies with our present and previous81,32, a4 findings is not known.…”
Section: Discussionmentioning
confidence: 90%
“…Much of the neurochemical data supporting this hypothesis originates from studies comparing the spontaneously hypertensive rat (SH-rat), which was established as an inbred strain by Okamoto and associates (see ref. 17), with rats of the parent Wistar-Kyoto strain (WK-rat) 3,12,22,24,26,31,32,34,35,37. Part of the available data concerns the possible participation of adrenaline-containing neurons in this effect 22, 24,31,32,34,35. It seems highly likely that noradrenaline is involved as wella, 14,22,31.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation